2011
DOI: 10.1007/s12237-011-9459-6
|View full text |Cite
|
Sign up to set email alerts
|

Life Histories, Salinity Zones, and Sublethal Contributions of Contaminants to Pelagic Fish Declines Illustrated with a Case Study of San Francisco Estuary, California, USA

Abstract: Human effects on estuaries are often associated with major decreases in abundance of aquatic species. However, remediation priorities are difficult to identify when declines result from multiple stressors with interacting sublethal effects. The San Francisco Estuary offers a useful case study of the potential role of contaminants in declines of organisms because the waters of its delta chronically violate legal water quality standards; however, direct effects of contaminants on fish species are rarely observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 135 publications
(161 reference statements)
1
75
0
Order By: Relevance
“…They attributed summer diatom blooms in Suisun Bay prior to 1987 to accumulation of phytoplankton biomass rather than a high growth rate (Cloern 1979;Cole and Cloern 1984 reported by Cole and Cloern (1984); the slight seasonal increase that we observed for P B M(24) occurred in parallel with the movement of the sampling area from Central Bay to Suisun Bay and the western Delta Cole and Cloern (1984) for spring. It has been hypothesized that growth rates of phytoplankton in the northern SFE have potentially decreased as a result of increased NH 4 loading (Dugdale et al 2007;, contaminants (Brooks et al 2012), and shifts in phytoplankton community composition (Lehman 2000;Glibert et al 2011). The decline in both P (24) reported by Alpine and Cloern (1992) was much higher than other estimates of P B M(24) reported for the SFE (Table 1) but similar to values reported for some other estuaries (e.g., Pennock and Sharp 1986).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…They attributed summer diatom blooms in Suisun Bay prior to 1987 to accumulation of phytoplankton biomass rather than a high growth rate (Cloern 1979;Cole and Cloern 1984 reported by Cole and Cloern (1984); the slight seasonal increase that we observed for P B M(24) occurred in parallel with the movement of the sampling area from Central Bay to Suisun Bay and the western Delta Cole and Cloern (1984) for spring. It has been hypothesized that growth rates of phytoplankton in the northern SFE have potentially decreased as a result of increased NH 4 loading (Dugdale et al 2007;, contaminants (Brooks et al 2012), and shifts in phytoplankton community composition (Lehman 2000;Glibert et al 2011). The decline in both P (24) reported by Alpine and Cloern (1992) was much higher than other estimates of P B M(24) reported for the SFE (Table 1) but similar to values reported for some other estuaries (e.g., Pennock and Sharp 1986).…”
Section: Discussionsupporting
confidence: 63%
“…Like many other urbanized estuaries around the world, the SFE has experienced perturbations in key ecosystem drivers, including sediment and nutrient loads (Schoellhamer 2011;Jassby 2008), quantity and diversity of toxic pollutants (Brooks et al 2012), decreased phytoplankton biomass, and a loss of diatoms (e.g., Alpine and Cloern 1992;Kimmerer 2004;Dugdale et al 2007), and changes in zooplankton and fish (Mueller-Solger et al 2002;Kimmerer 2005). Although the original authors of the light-utilization model for the SFE (Cole and Cloern 1984) predicted that the empirical efficiency factor y would likely respond to such changes, this parameter has been previously recalculated for the northern estuary only twice (Alpine and Cloern 1992;Jassby et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of Stockton, major cities in the Northern SFE and Delta do not carry out advanced secondary treatment and discharge N primarily in the form of NH 4 rather than NO 3 . As of 2006, 75% of the effluent released by Delta treatment plants was processed only to the secondary level (Brooks et al, 2011). Approximately 90% of the total N in the Northern SFE originates from a single point source, at the Sacramento Regional WTP (SRWTP), which discharges approximately 15 metric tons of N per day, largely as NH 4 , to the Sacramento River (Jassby, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Targeted research in the Delta and adjacent waters has shown that Delta water is often acutely or sublethally toxic to a range of aquatic organisms, particularly near sources of urban or agricultural discharge (Brooks et al 2012;Biales et al 2015).…”
Section: Nutrients Are Importantmentioning
confidence: 99%